Borrelia burgdorferi Escape Mutants That Survive in the Presence of Antiserum to the OspA Vaccine Are Killed When Complement Is Also Present - Solé, Mónica (American Society for Microbiology, 1998)
As an initial attempt to investigate the possible role of outer surface protein A (OspA) escape mutants of Borrelia burgdorferi in decreasing the efficacy of the OspA vaccine, mutants of the HB19 strain of B. burgdorferi sensu stricto were selected in vitro from an uncloned, low-passage-number isolate. The antiserum used for selection was obtained from rhesus monkeys that had been given a vaccine of the same formulation and dose, and by the same route of administration, as that given to humans in several trials. All of the mutants selected in liquid medium and subsequently cloned twice in solid medium expressed a single abundant protein of 28 to 34 kDa instead of both OspA and OspB. Depending on the mutant, this protein reacted strongly, weakly, or not detectably with the anti-OspA antibody used for selection. Analysis of the ospAB locus of each of four representatives from these three groups of mutants by PCR with oligonucleotide primers that hybridize to flanking regions of the ospAB operon, and of the corresponding phenotype with monoclonal antibodies that bind to the amino or carboxyl terminus of the OspA or OspB polypeptide, indicated that in all cases a deletion within the operon had occurred. Spirochetes from the four mutant strains chosen for further analysis could be killed in antibody-dependent, complement-mediated killing assays with the selecting anti-OspA antibody, despite their resistance to killing with this antibody in the absence of complement. Complement-mediated killing occurred at an antibody concentration higher than that required to kill wild-type spirochetes. If anti-OspA antibody acts only within the tick, where complement is probably ineffective due to tick-derived decomplementing factors, then OspA escape mutants, if infectious, could seriously diminish the efficacy of OspA vaccines. On the other hand, if the killing of B. burgdorferi with anti-OspA antibody also takes place within the human host, then our results indicate that chimeric/deletion escape mutants will be killed as well.